Entrepreneurially oriented in what? A business model approach to entrepreneurship. Issue 3 (17th August 2015) - Andersén, Jim; Ljungkvist, Torbjörn; Svensson, Lotten
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to illustrate and argue for the necessity of deconstructing the entrepreneurship concept by analyzing entrepreneurial orientation (EO) at various levels of the business model. Design/methodology/approach – Literature review supplemented with five illustrative cases. Findings – A business model approach to entrepreneurship enables identification of the component of the business model in which entrepreneurship was started. This has several implications for analysis of the EO-performance relationship and for the identification of antecedents to EO. Originality/value – The EO of firms has generally been analyzed at a generic level, i.e. the concept has been used to measure and analyze the overall entrepreneurship of firms. In this paper, the authors argue that EO can be present in various dimensions of a business and that firms can be entrepreneurial in certain areas and conservative in other areas.